Does Technological Diffusion Explain Australia's Productivity Performance? - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2008)
This paper analyzes the impact of product and labor market policies on technological diffusion and multi-factor productivity (MFP) in a panel of industries in 15 OECD countries over the period 1980 to 2003, with a special focus on Australia. We use a simple convergence empirical framework to show that, on average, convergence of MFP within industries across countries has slowed-down in the 1990s. In contrast, Australian industries have significantly caught-up with industry productivity best practices over the past 16 years, and have benefited from the diffusion of Information and Communication Technologies (ICTs). We show that reforms of both the labor and product markets since the early 1990s can explain Australia's productivity performance and adoption of ICTs.